Sleep pattern and sleep disorders among a sample of Malaysian children. Issue 3 (9th June 2013) - Firouzi, Somayyeh; Bee Koon, Poh; Noor, Mohd Ismail; Sadeghilar, Aidin
Abstract: Sleep problems and sleep disturbances have been associated with several heath‐related issues especially in children. However, there are limited data regarding sleep pattern and sleep disorders among Malaysian children. Subjects comprised 183 Malaysian children aged 6–12 years old. Children sleep habit questionnaires were proxy reported by the parents of the seven primary school children. Weight and height were measured and body mass index (BMI) was calculated accordingly. Data were analyzed and differences according to age, gender, body mass index, and area of living (urban and rural) were noted. There were no significant differences in sleep duration, bedtime, and wake up time between genders, area of living, or among different BMI categories. Sleep duration decreased as age increased. A total number of 41.5% of children did not get enough sleep with significant differences among different ages. Sleep disorder scores were significantly lower among children who are living in rural areas and in children with BMI at normal levels. The present data showed that these children sleep less than what they actually need and sleep disturbances are prevalent among those who are living in urban areas and also among overweight and obese children.